Photobiomodulation in the stability of dental implants (Research, Society and Development, 2024)
Photobiomodulation therapy (PBMT) promotes the stability of dental implants by using light to stimulate biological processes, accelerating bone and tissue healing. Studies show that PBMT increases osteoblast activity and angiogenesis, improving osseointegration. With anti-inflammatory and analgesic properties, PBMT reduces postoperative discomfort, especially benefiting patients with compromised healing, such as diabetics or those with osteoporosis. Thus, the aim of this narrative literature review is to present PBMT as a therapeutic option for the stability of dental implants. PBMT is promising in dentistry, especially for stabilizing dental implants and promoting osseointegration. Using low-irradiance light, PBMT stimulates biological processes and accelerates healing without thermal damage. Studies show benefits in the initial stability of implants. However, standardizing treatment protocols is necessary to ensure consistent results and avoid adverse effects.